Characterization of glucose‐binding proteins isolated from health volunteers and human type 2 diabetes mellitus patients. Issue 11 (20th July 2021) - Chen, Wentian; Zhong, Yaogang; Shu, Jian; Yu, Hanjie; Chen, Zhuo; Ren, Xiameng; Hui, Ziye; Li, Zheng
Abstract: Glucose is one of the most important monosaccharides. Although hyperglycemia in type 2 diabetes mellitus (T2DM) lead to a series of changes; however, little is known about the alterations of serum proteins in T2DM, especially those proteins with glucose affinity. In this study, the glucose‐binding proteins (GlcBPs) of serum were isolated from 30 health volunteer (HV) and 30 T2DM patients by glucose‐magnetic particle conjugates (GMPC) and identified by mass spectrum analysis. Gene ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) indicated the main gene annotations and pathways of this GlcBPs, while Motif‐X webtool provided the potential glucose‐binding domains. Further docking analysis and glycan microarray were used to understand the interaction between the glucose and glucose‐binding domains. A total of 149 and 119 GlcBPs were identified from HV and T2DM cases. Four hundred and sixty‐eight GO annotations in 165 identified GlcBPs were available, while the majority involved in cellular processes and binding function. A short peptide, EGDEEITCLNGFWLE, which was derived from the Motif‐X analysis, presented a high‐binding ability to the glucose from both docking analysis and glycan analysis. GMPC provides a powerful tool for GlcBPs isolation and indicates the alteration of GlcBPs in T2DM.